PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN KAS TERHADAP RETURN ON ASSET PADA BANK DEVISA SWASTA NASIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2017 - Dody Firman; Hade Chandra Batubara; Mhd. Alpido Sahputra (Prosiding Seminar Nasional USM, 2019)
The purpose of this research is to test and analyze the influence of receivables turnover on Return On Assets (ROA), cash turnover against Return On Assets (ROA), and stomach receivables and cash turnover against Return On Assets (ROA), both partially and simultaneously on the national private foreign exchange Bank listed on the Indonesia Stock Exchange period 2013-2017. The approach used in this research is an associative approach. The population in this study is the entire national private foreign exchange Bank listed on the Indonesia Stock Exchange while a sample meets the criteria for the sample withdrawal of observations conducted over five years as many as seven national private foreign exchange banks Listed on the Indonesia Stock Exchange. The data collection techniques in this study used documentation techniques. The data analysis techniques in this study used the classical assumption test, double regression, hypothesis test (t test and F test), and coefficient of determination. The data processing in this study used SPSS software program (Statistic Package for the Social Sciens) version 24.00. The results of this study proved that it is partially known that the rotational turnover has no significant effect on Return On Assets. It is partially known that turnaround has no significant effect on Return On Assets. Simultaneously it is known that the rotation of the turnover and the cash turnover together has no significant effect on Return On Assets.